Black hole thermodynamics - Fernandes, Tiago (Cadernos de Astronomia, 2023)
Black holes are present everywhere in our universe. According to general relativity, these objects are classical and don’t emit any radiation, they are in fact black. Nevertheless, when quantum fields are considered, it turns out that black holes are thermodynamic objects and so there are not that black. In the article, we briefly give the classical description of black holes and its four laws of mechanics. We also present the first papers that pushed foward the idea that black holes are thermodynamic objects. At last, we present the formalism that allows the treatment of thermodynamics of spacetimes containing black holes and we also present very briefly the current investigation in this area.